The Relationship of Integrated Antenatal Care (ANC) Examination to The Incidence of Low Birth Weight (LBW) at Harapan Bunda Hospital, Batam City - Suhada Suhada; Anisya Selvia; Dedy Siska (MEDICA (International Medical Scientific Journal), 2024)
Low birth weight infants (LBW) are infants who weigh less than 2500 grams at birth regardless of the gestation period and can occur in full-term or premature infants. LBW is one of the most common causes of infant mortality in Batam City in 2022. This study aims to determine the relationship of integrated antenatal care examination to the incidence of LBW at Harapan Bunda Hospital Batam in 2023. This type of research uses a retrospective study with secondary data in the form of medical records of laboring mothers in January-October 2023 taken at Harapan Bunda Hospital. The population used in this study were mothers who gave birth to LBW babies. Sampling with total sampling and the number of research samples obtained was 96 samples. Data analysis used was univariate and bivariate analysis. Bivariate analysis used the Chi-Square statistical test. The results showed that 38 mothers had complete antenatal care who experienced LBW and 58 mothers who had incomplete antenatal care who experienced LBW. There is a relationship between antenatal care and the incidence of low birth weight at Harapan Bunda Hospital Batam in 2023 with a p-value of 0.027. It is expected that health workers and midwives can socialize with the community, especially pregnant women, about the importance of conducting antenatal care visits at least 6 times during pregnancy.